0114 Evolution of brain circuits supporting spatial navigational memory across sleep. (25th May 2022) - Parekh, Ankit; Kam, Korey; Valencia, Daphne; Fleysher, Lazar; Fakhoury, Ahmad; Castillo, Bresne; Rapoport, David; Ayappa, Indu; Varga, Andrew
Abstract: Introduction: Systems consolidation is one of the major theories of sleep's function in memory. Sleep is thought to be important in integrating and distributing hippocampal information to cortical structures such that there is less hippocampal activation, while at the same time increasing striatal activation, upon subsequent experience in the same environment that co-occurs with improved performance. Here we sought to examine the evidence supporting systems consolidation across sleep in spatial navigational memory. Methods: 15 subjects (28±5 yrs., 8 female) with no prior videogame experience and no sleep disorders were recruited to undergo spatial navigational memory testing before and after a night of sleep. Spatial navigational memory was tested across two functional MR (fMRI) sessions (approx. 7PM and 8AM) separated by in-lab nocturnal polysomnography (NPSG) measured sleep using a virtual 3D Maze. Each fMRI session consisted of six runs: three maze trials interleaved with three control trials. During maze trials participants were instructed to reach a prespecified goal as quickly as possible, whereas during the control trials, participants were instructed to navigate a Z-shaped corridor with no prespecified goal. fMRI data was analyzed in 2-step procedure using Analysis of Functional Neuroimages (AFNI) software package. To estimate hippocampal activity during fMRI, parameter estimates of the %change in blood-oxygen-level-dependent (BOLD) signal using the contrast maze-control were used as the primary metric. Regions of interest were limited to the bilateral hippocampus, parahippocampal gyrus, caudate, and putamen using the Eickhoff-Zilles macro labels from the MNI-N27 template. Results: During in-lab NPSG, participants experienced a total sleep time of 6.1±1.1 hrs (8.7±2.9%stage1, 51.2±7.6%stage2, 21.8±8.5%stage3, 18.1±6%REM). Within subjects, compared to pre-sleep, a significantly lower activation of the bilateral hippocampus and parahippocampal gyrus was observed post-sleep (evening-morning %change=0.26±0.11, p<0.05). Compared to pre-sleep, caudate and putamen activity was not significantly different post-sleep (evening-morning %change=-0.02±0.04, p=0.5). Greater evening hippocampal activity was associated with greater change in maze completion times across sleep (rho=0.54, p=0.04). Conclusion: In young healthy adults, a night of uninterrupted sleep supports redistribution of hippocampal contribution toward spatial navigation. Greater initial pre-sleep hippocampal contribution was associated with improved recall of spatial navigational memory after a night of sleep. Support (If Any): NIH R21AG059179, R01AG056682, K25HL151912